PROFESSIONAL COMPETENCES OF EMPLOYEES IN THE FACILITIES OFFERING PROTECTION AND SUPPORT TO VICTIMS OF DOMESTIC VIOLENCE - Lepir, Ljubo; Šćepović, Dragana (Politeia, 2021)
The key resource on which the efficiency of the system of protection and support of victims of domestic violence depends is related to the number and training of professionals who deal with this phenomenon in their work. Qualifications and competencies of professionals who are directly engaged in cases of domestic violence are the key to success in prevention, legal prosecution of perpetrators of violence, but as well in providing direct support to victims of violence. The research focused on that segment of public systems that deal with domestic violence. Through the analysis of the basic elements of competencies of employees in public systems, this paper gives an overview of the state of human resources from the aspect of possessing expertise and professional knowledge, experience and abilities. In a sample of 283 respondents employed in the police, social work centres, health centres and primary schools in six municipalities in the northern part of Republic of Srpska, through the analysis of basic elements that determine the state of professional resources, it was concluded that existing resources are not sufficiently developed and directed towards the area of domestic violence. The obtained results showed that there is no practice of professional training for work in the field of domestic violence, and the self-perception of employees in public institutions is not related to objective indicators of their abilities and skills they possess. Practical action is focused mainly on minimal actions arising from the implementation of the most necessary legal procedures, while the expressed interest of professionals employed in public institutions opens space for their professional development and providing greater functionality of the system in providing protection and support to victims of domestic violence.